Communication Preferences of Politically Active Agricultural Leaders - Ricky Telg; Adam Basford; Tracy Irani (Journal of Applied Communications, 2005)
Agricultural associations and advocacy organizations have begun to use the Internet to establish more effective online grassroots help for lobbying efforts, yet little research has been conducted to ascertain communications technology preferences and willingness of members to use the Internet as a communications tool. To address this issue, a descriptive survey was mailed to a purposive sample (N= 814) of members holding leadership positions in the Florida Farm Bureau; 268 members responded to the survey, for an overall response rate of 33%. Respondents used communication technologies frequently, expressed competence in basic technology procedures, and actively communicated with elected officials at the local, state, and federal levels. Respondents indicated that they preferred to receive and send information through the mail, and that they were most inclined to take a strong role in communicating with officials when policies negatively impacting agriculture were being considered. Respondents felt that e-mail would be an adequate substitute for some forms of communication but were less likely to say that e-mail would be a good substitute for more personal methods of communication, such as telephone conversations or face-to-face meetings. These findings suggest that where it is important to communicate en masse rapidly, the online method may have advantages. However, a “one-way-fits-all” online method of communicating with elected officials may not be the most effective communication method; more personal ways of communicating, especially at the local and state levels, may still be best for some issues.